A Novel Class of Dual-Acting DCH-CORMs Counteracts Oxidative Stress-Induced Inflammation in Human Primary Tenocytes - Federico Appetecchia; Sara Consalvi; Emanuela Berrino; Marialucia Gallorini; Arianna Granese; Cristina Campestre; Simone Carradori; Mariangela Biava; Giovanna Poce (MDPI AG, 2021)
Carbon monoxide (CO) can prevent cell and tissue damage by restoring redox homeostasis and counteracting inflammation. CO-releasing molecules (CORMs) can release a controlled amount of CO to cells and are emerging as a safer therapeutic alternative to delivery of CO in vivo. Sustained oxidative stress and inflammation can cause chronic pain and disability in tendon-related diseases, whose therapeutic management is still a challenge. In this light, we developed three small subsets of 1,5-diarylpyrrole and pyrazole dicobalt(0)hexacarbonyl (DCH)-CORMs to assess their potential use in musculoskeletal diseases. A myoglobin-based spectrophotometric assay showed that these CORMs act as slow and efficient CO-releasers. Five selected compounds were then tested on human primary-derived tenocytes before and after hydrogen peroxide stimulation to assess their efficacy in restoring cell redox homeostasis and counteracting inflammation in terms of PGE2 secretion. The obtained results showed an improvement in tendon homeostasis and a cytoprotective effect, reflecting their activity as CO-releasers, and a reduction of PGE2 secretion. As these compounds contain structural fragments of COX-2 selective inhibitors, we hypothesized that such a composite mechanism of action results from the combination of CO-release and COX-2 inhibition and that these compounds might have a potential role as dual-acting therapeutic agents in tendon-derived diseases.